PENGARUH IMPLEMENTASI APLIKASI KINERJA ASN DIGITAL TERHADAP PRODUKTIVITAS PEGAWAI DI DINAS PERUMAHAN RAKYAT, KAWASAN PEMUKIMAN DAN LINGKUNGAN HIDUP KABUPATEN PEGUNUNGAN ARFAK - Krisdianty, Putri; Lambi, Manuel; Hammar, Yunus Tekad K.R (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the effect of digital ASN performance application usage on employee productivity at the Department of Public Housing, Settlement Area and Environment of Pegunungan Arfak Regency. The research method used a quantitative approach with simple linear regression analysis. Data were collected from 67 respondents using Total Sampling technique through Likert-scale questionnaires. The results show that digital ASN performance application usage has a positive and significant effect on employee productivity, with a regression coefficient of 0.673, t-value of 10.398 (t-table = 1.997), and significance of 0.000. The coefficient of determination (R²) of 0.624 indicates that 62.4% of the variation in employee productivity can be explained by digital performance application usage, while the remainder is influenced by other factors. Implications for policymakers include the need for improved digital literacy, continuous training, and strengthened technological infrastructure to ensure optimal implementation of digital performance applications and meaningful improvements in ASN productivity.